PENDAMPINGAN PENENTUAN PRIORITAS PELATIHAN BAGI PETERNAK BABI DI DESA WAE LOLOS KABUPATEN MANGGARAI BARAT - Wigbertus Gaut Utama; Roselin Gultom; Hendrikus Demon Tukan; Puspita Cahya Achmadi (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
One form of empowering farmers is providing continuous and contextual training. In its implementation, the training must be truly based on the needs of the farmers themselves. This is in line with the "bottom up" approach in community development. This Community Service Activity was held to help pig farmers in Wae Lolos Village, West Manggarai, in determining their own type and priority of training that needs to be carried out according to the farmers' conditions. This community service activity was arranged using the 'brainstorming' method, in which the participant was set up in small group discussions. The strategies taken were determined based on the SWOT analysis, then each strategy was distributed into training categories. Based on the discussions and analyzes that have been carried out with the farmers, the number of training matters has been determined, the first priority being training in the socio-economic field; second, feed and nutrition; third, production; and fourth, health sector. In addition to these four scopes, the results of this Community Service activity also recommend the importance of improving and redesigning the institutional aspects of animal husbandry at the community level in Wae Lolos Village